Evaluation of Urinary Calculi by Infrared Spectroscopy - Mehrsai, Abdolrasool; Taghizadeh Afshari, Ali; Zohrevand, R; Djaladat, Hooman; Steffes, H J; Hesse, A; Pourmand, Gholamreza (Urology Journal, 2009)
Purpose: To analyze urinary calculi composition and its relationship with gender, age, calculus weight, color, and location. Materials and Methods: Two hundred and forty one patients with urinary calculus, who had undergone open lithotomy from June 1999 to April 2001, were enrolled in this prospective study which was performed by Tehran and Oroomieh Medical Sciences Universities. The calculi compositions were analyzed by infrared spectroscopy in Bonn University. Statistical analyses were made by paired t test Results: One hundred and forty five males with a mean age of 40.4 years and 96 females with a mean age of 42.5 years were enrolled in this study. Mean calculus weight was 4.28 gr. Mean calculus number was 4.33. Thirty four (14.1%) calculi were pure (carbonate apatite: 2, brushite: 1, uric acid: 19, cystine: 3, weddellite: 6, mono-NH4-urate: 2, struvite: 1), 207(85.6%) were mixed and none of them contained octa-ca-phosphate, apatite, newberyte, 2,8-dihydroxyadenine, mono-Na-urate, or xanthine. Weddellite was found in 77% of calculi. It comprised more than 50% of them in 26% of cases. Whewellite crystals were found in 78% of calculi. It comprised more than 50% of them in 46% of cases. The most common pure calculus was uric acid and the most common component of calculi was whewellite followed by weddellite. Conclusion: Although there is no comprehensive study on urolithiasis incidence and prevalence in Iran, it can be concluded that whewellite and weddellite may be the most common components of urolithiasis in Iran and uric acid calculi are the most common pure calculi. There was no significant difference in calculi composition in our study.